Efficacy of the Full Mesenchymal Stromal Cell Secretome versus Purified Small Extracellular Vesicles in Preclinical Models of Erectile Dysfunction: A Systematic Review and Parallel Meta-Analysis - Victor Jeremia Syaropi Simanjuntak; Ishak Andreas Soritua Lumban Gaol; Erlangga Pradipta H; Dimas Sindhu Wibisono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Acellular therapies from Mesenchymal Stromal Cells (MSCs), including the full secretome (conditioned medium, CM) and purified small extracellular vesicles (sEVs), are promising restorative treatments for erectile dysfunction (ED). It remains unknown if the therapeutic benefit is driven by the complete secretome or if purified sEVs are the primary, sufficient component. This study aimed to systematically review and meta-analyze the preclinical evidence. Methods: We conducted a systematic review and parallel meta-analysis adhering to PRISMA guidelines. PubMed, Scopus, and Web of Science were searched from January 1st, 2014, to July 31st, 2025. Studies were eligible if they were preclinical ED models evaluating MSC-CM or purified sEVs against a control. Two parallel meta-analyses were performed using a random-effects model. Primary outcomes were erectile function (Intracavernous Pressure / Mean Arterial Pressure ratio; ICP/MAP) and histopathology (Smooth Muscle / Collagen ratio; SM/Col). Results: Our search yielded 1,942 records, with 87 full-text articles assessed. After applying strict PICO criteria, 7 primary studies were eligible for the meta-analysis (3 secretome, 4 sEVs). The overall risk of bias was moderate to high (0% allocation concealment). No studies directly compared secretome versus sEVs. The first meta-analysis (Secretome vs. Control, 3 studies, 4 data points, n=70) demonstrated a large, significant improvement in ICP/MAP (Standardized Mean Difference [SMD]: 2.40; 95% CI [1.65, 3.15]; p-value < 0.001), with extreme heterogeneity (I-squared=85%). The second meta-analysis (sEVs vs. Control, 4 studies, n=68) also showed a large, significant improvement (SMD: 2.75; 95% CI [1.90, 3.60]; p-value < 0.001), also with extreme heterogeneity (I-squared=88%). Conclusion: Both the full MSC secretome and purified sEVs demonstrate large, significant therapeutic effects. However, this quantitative conclusion is severely limited by the exceptionally small number of studies and the profound biomolecular heterogeneity (in cell source and purification) that invalidates direct comparison. The primary finding remains the total lack of comparative data.